A textbook of solid state drives - Gnanavadivel, J (Anuradha Publications, 2011)
The main aim of this book is to provide a basic concepts of drive characteristics, controlled rectifiers fed DC drives, chopper fed DC drives, design of controller for drive, three phase induction motor drives and synchronous motor drives in a lucid way with neat sketches and waveforms. each chapter contains short question and answers to get complete knowledge of the subject. Large number of worked examples are added to the clarity of the subject matter.